Protective effects of melatonin against fluoride-induced oxidative stress in rats at high altitude - VIVEK, PRINCE; BHARTI, VIJAY K; KALIA, SAHIL; GIRI, ARUP; KUMAR, KRISHNA; KUMAR, BHUVNESH (The Indian Journal of Animal Sciences, 2019)
This study was conducted to evaluate the protective effects of melatonin against fluoride-induced oxidative stress-mediated haematological and biochemical changes in rat at high altitude. Adult male Wistar rats (6) were given the basal diet and drinking water ad lib. for first 7-days which was considered as the control period. Thereafter, they were exposed to NaF (@ 50 ppm) per-oral through drinking water for the next 14 days followed by melatonin treatment (@ 15 mg/kg BW, p.o.) for the next 14 days. The result showed induction of oxidative stress during NaF treatment alone, which caused significant increase in alkaline phosphatase (ALP), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) activity, and % inhibition of DPPH, MDA, and water intake. Whereas, total antioxidant capacity (FRAP) and body weight gain were significantly reduced during NaF exposure. Haemogram analysis indicated significant decrease in haemoglobin, packed cell volume, erythrocytes, lymphocytes, platelets count, whereas increase in MCH, monocytes, neutrophil, and eosinophil during NaF exposure. However, melatonin administration after 14 days of fluoride treatment resulted in significant amelioration of adverse changes occurred in different blood-biochemical parameters and also increased the total antioxidant status. Notably, the body weight gain improved during melatonin administration. These findings indicated induction of oxidative stress-mediated adverse change in haematology and biochemical parameters, and amelioration effect of oral dose of melatonin in rats under high altitude stress condition. Hence it can be concluded that melatonin acts as a potent antioxidant agent, which may be orally supplemented for amelioration of fluoride-mediated oxidative stress even under prevalent high altitude stress.